2014
DOI: 10.1136/lupus-2014-000062
|View full text |Cite
|
Sign up to set email alerts
|

Increased Th17 cells in flow cytometer-sorted CD45RO-positive memory CD4 T cells from patients with systemic lupus erythematosus

Abstract: ObjectivesTh17/IL-17 dysregulation is involved in human autoimmunity, and recent evidence suggests the character of long-lived differentiated memory cells in Th17. By directly measuring the peripheral blood mononuclear cells (PBMC), elevated circulating frequencies of Th17 cells have been reported in systemic lupus erythematosus (SLE) with inconsistent results regarding the correlation with disease activities. In this study, the association between circulating Th17 frequencies and disease activities or laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Along with a reduced number of Treg cells, elevated Th17 levels have been reported in the same patient pool. Thereby augmented Th17 numbers positively correlated with disease activity . Underlying the significance of an imbalance in the ratio between both Th subsets, Ma et al .…”
Section: Systemic Lupus Erythematodesmentioning
confidence: 99%
“…Along with a reduced number of Treg cells, elevated Th17 levels have been reported in the same patient pool. Thereby augmented Th17 numbers positively correlated with disease activity . Underlying the significance of an imbalance in the ratio between both Th subsets, Ma et al .…”
Section: Systemic Lupus Erythematodesmentioning
confidence: 99%
“…Thus, PNS reversed the P-gp-mediated SR by suppressing the SIRT1/ FoxO1/MDR1 signalling cascade. An increased frequency of Th17 cells was found in lupus, together with a positive correlation to the SLEDAI [55]. Th17 cells are related to SR.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, we also found that IL22, which together with IL17A and IL17F belongs to the Th17 effector molecules, was the most obviously differentially expressed gene, at 521 folds higher than the NC group. Generally, the production of IL17A has been recognized as the marker of Th17 cell differentiation [44][45][46][47]. In order to determine whether the high levels of pro-inflammatory cytokines were caused by Th17 cell differentiation after BVDV infection, we measured the Th17 cell differentiation by flow cytometry and the production of IL17A by qRT-PCR and western blotting.…”
Section: Discussionmentioning
confidence: 99%